Environmental Conditions, Irrigation Reuse Pits, And The Need For Restoration In The Rainwater Basin Wetland Complex, Nebraska - Robichaux, Rex; Harrington, Lisa M.B. (My University, 2010)
Many of the processes of social and economic change in rural areas of America in the last century have had significant negative environmental impacts (Woods, 2005). The conversion of native grasslands and woodlands to farmland is a phenomenon that has been observed the world over (Foley et al., 2005). The growing demands of agriculture have transformed land cover at a global scale (Goudie, 2006). It is estimated that, globally, grasslands have lost approximately 19.4 million sq km from their pre-agricultural extent. According to Goldewijk (2001), in the past 300 years, areas of cropland and pasture have increased by around five to six fold. The loss of wetlands on a global scale is cause for serious concern. Wetlands cover about 6 percent of the earth’s surface, even though they tend to occur in relatively small and often geographically isolated patches. However they also are responsible for about one quarter of the Earth’s net primary productivity, and provide crucial wintering, breeding, and refuge areas for wildlife (Goudie, 2006). With these facts in mind, it becomes even more alarming that the world has lost up to 50 percent of its wetlands since 1900; the United States alone has lost approximately 54 percent of its native wetland habitat, mostly through the conversion to farmland (Goudie, 2006).
Keywords: Wetlands; Rainwater Basin Wetland Complex; Farmland; Cropland; Wildlife; Migratory birds; Restoration